Residual force enhancement during multi-joint leg extensions at joint- angle configurations close to natural human motion - Paternoster, F. K.; Seiberl, W.; Hahn, D.; Schwirtz, A. (Journal of Biomechanics, 2016)
The isometric steady-state forces following lengthening are greater than those produced at the same muscle length and activation level but without prior lengthening. Although residual force enhancement (RFE) has been investigated across a range of conditions, its relevance for daily human movement is still poorly understood. We aimed to study RFE in a setup imitating daily activity, i.e., submaximal activation of the lower extremity`s muscles with slightly flexed knee joints comparable to human walking.